Gambaran Pasca Kemerdekaan pada Naskah Drama Awal&Mira - Pandiangan, Angellica Minarti Martogi; Andhini, Alfira; Purnamasari, Widiyani Kuspi; Nugroho, Rudi Adi (Kajian Bahasa dan Sastra (KABASTRA), 2023)
This study aims to present a post-independence picture that is displayed in literary and artistic works, examples of drama scripts. As can be seen in the drama script "Awal & Mira" by Utuy Tatang Sontani which has a post-independence setting. The research method used is the personality approach method and the sociology approach. The result of this research is that Indonesia which was already independent at that time was not yet fully independent as described in the drama script "Awal & Mira" which raised the suffering of post-independence Indonesian citizens.